Anti-CD19 chimeric antigen receptor T-cell therapy for adult Philadelphia chromosome-positive acute lymphoblastic leukemia: Two case reports. Issue 51 (December 2016) - Zhu, Yang-min; Wu, Zhao; Tan, You-ping; Du, Yuan-yuan; Liu, Zhi; Ou, Rui-ming; Liu, Shuang; Pu, Cheng-fei; Jiang, Jing; Wang, Jin-ping; Xiao, Lei; Zhang, Qing
Abstract: Rationale: The presence of the Philadelphia chromosome (Ph) in acute lymphoblastic leukemia (ALL) has been associated with a high risk of disease relapse and a poor prognosis. Allogeneic hematopoietic stem cell transplantation (HSCT) is an established treatment for adults with Ph-positive ALL, but relapse remains the primary cause of treatment failure, and is associated with an extremely poor prognosis. The emergence of resistance to tyrosine kinase inhibitors (TKIs) poses a challenge for patients with disease relapses after initial treatment with TKI-containing regimens. Patient concerns: Two patients with TKI-resistant recurrent Ph-positive ALL. Diagnoses: Ph-positive ALL. Interventions: Anti-CD19 CAR T-cell infusion. Outcomes: One patient's bone marrow blasts decreased significantly, and the other reached negative minimal residual disease (MRD). However, we first recorded the development of new-onset acute graft-versus-host disease (aGVHD) after anti-CD19 CAR T-cell infusion in a patient who received allogeneic HSCT. Our 2 case reports also demonstrate the efficacy of anti-CD19 CAR T-cell therapy in the treatment of TKI-resistant Ph-positive ALL. Lessons: Our report suggests that anti-CD19 CAR T-cell therapy may be a promising option for the treatment of relapsed Ph-positive ALL after conventional chemotherapy or allogeneic HSCT. However, caution is due given the possibility of the adverse effects of cytokine release syndrome (CRS)-induced aGVHD for patients receiving allogeneic HSCT. Abstract : Supplemental Digital Content is available in the text